Testing Farmers’ Perception of Climate Variability: A Case Study from Kirtipur of Kathmandu Valley - Poudel, Jiban Mani (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
In the 21st century, global climate change has become a public and political discourse. However, there is still a wide gap between global and local perspectives. The global perspective focuses on climate fluctuations that affect the larger region; and their analysis is based on long-term records over centuries and millennium. By comparison, local peoples’ perspectives vary locally, and local analyses are limited to a few days, years, decades and generations only. This paper examines how farmers in Kirtipur of Kathmandu Valley, Nepal, understand climate variability in their surroundings. The researcher has used a cognized model to understand farmers’ perception on weather fluctuations and climate change. The researcher has documented several eyewitness accounts of farmers about weather fluctuations which they have been observing in a lifetime. The researcher has also used rainfall data from 1970-2009 to test the accuracy of perceptions. Unlike meteorological analyses, farmers recall and their understanding of climatic variability by weather-crop interaction, and events associating with climatic fluctuations and perceptions are shaped by both physical visibility and cultural frame or belief system. DOI: http://dx.doi.org/10.3126/hn.v11i1.7200 Hydro Nepal Special Issue: Conference Proceedings 2012 pp.30-34